Effect of an Oral Iron(III)-hydroxide Polymaltose Complex on Tetracycline Pharmacokinetics in Patients with Iron Deficiency Anemia - Potgieter, Maria A.; Pretorius, Sybrand G.; Jacobs, Yvonne L.; Venter, Cornea; Venter, Jan L.; Geisser, Peter (Arzneimittelforschung, 2007)
The study was carried out as an open-label, but laboratory-blind, single-dose, single-centre, randomized, two-period crossover study. Twenty-two patients with iron deficiency anemia completed the study. The study consisted of two treatment phases of 36 h, separated by a washout period of between 6 and 14 days. The two treatments were given orally. The reference treatment was tetracycline (CAS 60-54-8) alone (2 x 250 mg capsules) and the test treatment was iron(III)-hydroxide polymaltose complex (IPC, Maltofer©) together with tetracycline (2 x 250 mg capsules).IPC had no pharmacokinetic effect on the rate of absorption of tetracycline. With concomitant administration of tetracycline and IPC sufficiently high tetracycline concentrations, to ensure bacteriostasis, will be reached. An inhibitor effect of IPC to the tetracycline absorption, as it is known for ferrous salts, could not be observed.
Keywords: Antianemic drugs; CAS 60-54-8; Iron deficiency anemia; Iron(III)-hydroxide polymaltose complex, in vivo study, pharmacokinetics; Maltofer©; Tetracycline